Self-Tuning Insulin Adjustment Algorithm for Type 1 Diabetic Patients based on Multi-Doses Regime - D. U. Campos-Delgado; R. Femat; M. Hernández-Ordoñez; A. Gordillo-Moscoso (Applied Bionics and Biomechanics)
A self-tuning algorithm is presented for on-line insulin dosage adjustment in type 1 diabetic patients (chronic stage). The algorithm suggested does not need information of the patient insulin–glucose dynamics (model-free). Three doses are programmed daily, where a combination of two types of insulin: rapid/short and intermediate/long acting is injected into the patient through a subcutaneous route. The doses adaptation is performed by reducing the error in the blood glucose level from euglycemics. In this way, a total of five doses are tuned per day: three rapid/short and two intermediate/long, where there is large penalty to avoid hypoglycemic scenarios. Closed-loop simulation results are illustrated using a detailed nonlinear model of the subcutaneous insulin–glucose dynamics in a type 1 diabetic patient with meal intake.